Enhanced Corporate Governance for Mutual Funds: A Flawed Concept that Deserves Serious Reconsideration - Martin E. Lybecker (Washington University Law Quarterly, 2005)
Mutual funds are the most popular retail investment in America, a testament to the simplicity and transparency of the mutual fund concept. A mutual fund investor owns a share of common stock issued by a company that invests in debt or equity securities issued by other operating companies. Like operating companies, a mutual fund distinguishes itself by its business objective—for example, to exceed the Standard & Poor’s 500 Index (an equity fund), to match the Lehman Brothers Aggregate Bond Index (a bond fund), or to maintain a current net asset value of $1.00 per share (a money market fund). Unlike an operating company that is managed by its officers and employees, most mutual funds are managed by an external investment adviser, pursuant to a contract. In recognition of the obvious conflict of interest between a mutual fund and its investment adviser because of or resulting from that contract, the Investment Company Act of 1940 (“Investment Company Act”) has always required that at least forty percent of the members of the mutual fund’s board of directors be independent. In July 2004, the Securities and Exchange Commission (“SEC” or “Commission”), in a three-to-two vote, amended certain existing exemptive rules (the “Corporate Governance Amendments”) to require that no less than seventy-five percent of the members of a mutual fund’s board of directors be independent, that the chairman of the board of directors be an independent director, and that the board of directors engage in certain specific corporate governance practices. This Article will argue that the Commission’s decision to adopt the Corporate Governance Amendments was without statutory authority and usurped the proper legislative role of Congress, was not adequately justified, and will be of questionable efficacy.
Keywords: Corporate governance; Mutual funds; Boards of directors; Mutual fund industry; Mutual fund managers; Investment Company Act of 1940; United States